Genetic Engineering of Filamentous Fungi for Efficient Protein Expression and Secretion - Wang, Qin; Zhong, Chao; Xiao, Han (Frontiers in Bioengineering and Biotechnology, 2020)
Filamentous fungi are considered as unique cell factories for protein production due to the high efficiency of protein secretion and superior capability of post-translational modifications. In this review, we firstly introduce the secretory pathway in filamentous fungi. We next summarize the current state-of-the-art works regarding how various genetic engineering strategies are applied for enhancing protein expression and secretion in filamentous fungi. Finally, in a future perspective, we discuss the great potential of genome engineering for further improving protein expression and secretion in filamentous fungi.